The Creation as a Method of Group Integration of People with ASD - I.Y. Suvorova (Moscow State University of Psychology and Education, 2019)
The article is devoted to psychological component of creation and its role in social integration of people with ASD. The analysis of creation as the process and as a result is presented. The author makes a conclusion that a person organizes an inner world and strengthens his/her Self as well as is being integrated into the work group. The application of the Self and the integration into the work group are the main problems for people with ASD. There are two cases which demonstrate reduction of anxiety, rising of personal subjectivity and the building of more differentiated boundaries of Self dew to creation. The work was conducted in the Technological College № 21 in Moscow.